Real Polynomial Maps and Singular Open Books at Infinity - Santos, Raimundo N. Araújo Dos; Chen, Ying; Tibăr, Mihai (MATHEMATICA SCANDINAVICA, 2016)
We provide significant conditions under which we prove the existence of stable open book structures at infinity, i.e. on spheres $S^{m-1}_R$ of large enough radius $R$. We obtain new classes of real polynomial maps $\mathsf{R}^m → \mathsf{R}^p$ which induce such structures.